Asian Multinational Phase II Study of Darinaparsin in Patients with Relapsed or Refractory Peripheral T-Cell Lymphoma - Fukuhara, Noriko; Kim, Won Seog; Yoon, Dok Hyun; Negoro, Eiju; Yamamoto, Kazuhito; Uchida, Toshiki; Izutsu, Koji; Terui, Yasuhito; Nakajima, Hideaki; Ando, Kiyoshi; Suehiro, Youko; Kang, Hye Jin; et al. (Blood, 2021)
Background: Darinaparsin is a novel organic arsenic compound composed of dimethylated arsenic linked to glutathione. In two phase I studies including Japanese and Korean patients with relapsed or refractory peripheral T-cell lymphoma (PTCL), darinaparsin was well tolerated and demonstrated potential efficacy (ASH2015 Abstract #2714 and Jpn J Clin Oncol. 2021, 51:218). The efficacy, safety and pharmacokinetics of darinaparsin in Asian patients with relapsed or refractory PTCL were evaluated in a multinational phase II study. Methods: Eligible patients had histologically confirmed PTCL not otherwise specified (PTCL-NOS), angioimmunoblastic T-cell lymphoma (AITL) or anaplastic large cell lymphoma (ALCL), which had relapsed from or were refractory to one or more prior regimen with systemic chemotherapy. Darinaparsin was intravenously administered for 5 consecutive days at 300 mg/m 2/day every 3 weeks. The primary endpoint was the overall response rate (ORR) within 6 cycles of treatment. Tumor response was assessed based on computed tomography (CT) and fluorodeoxyglucose-positron emission tomography (FDG-PET) evaluation by central review according to the Revised Response Criteria for Malignant Lymphoma (J Clin Oncol. 2007, 25:579). Secondary endpoints included progression-free survival (PFS), overall survival (OS), toxicity, and pharmacokinetic parameter. This study was conducted in 25 sites in East Asia (13 in Japan, 6 in Korea, 5 in Taiwan, and 1 in Hong Kong). Results: A total of 65 patients (37, 19, 8 and 1 from Japan, Korea, Taiwan and Hong Kong, respectively) including 43 PTCL-NOS, 17 AITL and 3 ALK-negative ALCL; 45 males and 20 females, with a median age of 68 (range 28-85) years received darinaparsin. The median number of prior systemic chemotherapy regimens was 2 (range 1-11). Approximately 30% of patients did not have evidence of response to the most recent prior systemic therapy. The median number of cycles received darinaparsin was 3 (range 1-39). In 57 evaluable patients, the ORR as assessed by an independent efficacy assessment committee was 19% (11 of 57; 90% Confidence Interval (CI) 11.2-29.9), and the lower limit of the 90% CI exceeded the predefined 10% threshold (p=0.024, binomial test). The ORR was 16.2% (6 of 37) in the subjects with PTCL-NOS and 29.4% (5 of 17) in the subjects with AITL. None of the subjects with ALCL, ALK-negative responded. Of the 11 responders, 5 achieved a Complete Response (CR) (8.8%), and 6 had a Partial Response (PR) (10.5%). Eight of the 11 responders showed response by Cycle 3. The disease control rate defined as the proportion of patients who achieved CR, PR or Stable Disease (SD) was 46% (26 of 57, 90% CI 34.3-57.3), and more than half of the patients achieved tumor shrinkage (Figure 1). Median duration of response (DOR) was 3.8 months (90% CI 2.7-5.7). Four patients who had achieved SD or better continued the treatment with darinaparsin for more than 1 year, and median duration of treatment in these subjects was 28.6 months (range 14-41). Median PFS and OS were 3.3 months (90% CI 1.9-4.2) and 13.7 months (90% CI 9.9-18.6), respectively. Among all 65 treated patients, the incidence of adverse events (AEs) was 97%, and that of drug-related AEs was 68%. AEs with an incidence of ≥ 20% were pyrexia (42%), anemia (25%), thrombocytopenia (20%) and decreased appetite (20%). The incidence of ≥ Grade 3 AEs was 62%, and that of ≥ Grade 3 drug-related AEs was 29%. The common ≥ Grade 3 AEs were anemia (15%), thrombocytopenia (12%), neutropenia (12%), lymphopenia (9%) and leukopenia (9%). While electrocardiogram (ECG) QT prolongation at 3% was reported as drug-related AEs associated with cardiac toxicity, there were no substantial changes from baseline in the descriptive statistics of ECG parameters associated with darinaparsin treatment. There was no apparent ethnic difference in pharmacokinetic profiles of patients studied. Conclusions: Darinaparsin had clinical efficacy and was well tolerated in patients with relapsed or refractory PTCL. AEs were clinically acceptable and manageable. Darinaparsin is a potential option for the treatment of relapsed or refractory PTCL. Updated results of DOR PFS, OS, and long-term safety are being analyzed for presentation at the conference. [Display omitted] Fukuhara: Ono Pharmaceutical: Honoraria, Research Funding; Novartis: Honoraria; Nippon Shinyaku: Honoraria; Kyowa Kirin: Honoraria; Janssen: Honoraria; Incyte: Research Funding; HUYA Bioscience International: Honoraria; Eisai: Honoraria; Chugai Pharmaceutical: Honoraria, Research Funding; Celgene: Honoraria, Research Funding; Bayer: Research Funding; AbbVie: Honoraria; Takeda Pharmaceutical: Honoraria; Zenyaku Kogyo: Honoraria. Kim: Celltrion: Research Funding; Dong-A Pharmaceutical: Research Funding; Eisai: Research Funding; Johnson & Johnson: Research Funding; Kyowa Kirin: Research Funding; Roche: Research Funding; IGM Biosciences: Research Funding; Sanofi: Research Funding. Yamamoto: Nippon Shinyaku: Honoraria, Research Funding; Otsuka: Honoraria, Research Funding; Ono: Honoraria, Research Funding; Novartis: Honoraria, Research Funding; Sanofi: Honoraria; Solasia Pharma: Research Funding; SymBio: Honoraria, Research Funding; Takeda: Honoraria, Research Funding; Yakult: Honoraria, Research Funding; Zenyaku: Honoraria, Research Funding; Micron: Honoraria; IQIVA/Genmab: Research Funding; ADC Therapeutics: Honoraria; Chugai: Honoraria, Research Funding; Daiichi Sankyo: Honoraria; Eisai: Honoraria, Research Funding; IQIVA/Incyte: Research Funding; IQIVA/HUYA: Honoraria; HUYA: Consultancy; Janssen: Honoraria; Kyowa Kirin: Honoraria; Meiji Seika Pharma: Consultancy, Honoraria, Research Funding; MSD: Honoraria; Mundipharma: Research Funding; Bristol-Myers Squibb/Celgene: Honoraria, Research Funding; AstraZeneca: Honoraria, Research Funding; AbbVie: Honoraria, Research Funding. Izutsu: Novartis: Honoraria, Research Funding; Ono: Honoraria, Research Funding; Pfizer: Research Funding; Symbio: Honoraria, Research Funding; Allergan Japan: Honoraria; FUJI FILM Toyama Chemical: Honoraria; MSD: Research Funding; Janssen: Honoraria, Research Funding; Incyte: Research Funding; Genmab: Honoraria, Research Funding; Chugai: Honoraria, Research Funding; Beigene: Research Funding; Bayer: Research Funding; AstraZeneca: Honoraria, Research Funding; AbbVie: Honoraria, Research Funding; Yakult: Research Funding; Takeda Pharmaceutical: Honoraria, Research Funding; Kyowa Kirin: Honoraria, Research Funding; HUYA Bioscience International: Research Funding; Eisai: Honoraria, Research Funding; Daiichi Sankyo: Honoraria, Research Funding; Celgene: Honoraria, Research Funding. Terui: Ono Pharmaceutical: Speakers Bureau; MSD: Speakers Bureau; Janssen: Speakers Bureau; Esai: Speakers Bureau; Chugai Pharmaceutical: Speakers Bureau; Celgene: Speakers Bureau; AbbVie: Speakers Bureau; Takeda Pharmaceutical: Speakers Bureau. Ando: Astellas Pharma: Honoraria; Celgene: Honoraria; Chugai Pharmaceutical: Research Funding; Kyowa Kirin: Research Funding; Novartis: Honoraria; Takeda Pharmaceutical: Research Funding. Suehiro: Otsuka Pharmaceutical: Research Funding; Ono Pharmaceutical: Research Funding; Novartis: Research Funding; Nippon Shinyaku: Honoraria; Kyowa Kirin: Honoraria, Research Funding; Incyte: Research Funding; Eisai: Honoraria, Research Funding; Chugai Pharmaceutical: Honoraria, Research Funding; Celgene: Research Funding; Bristol-Myers Squibb: Honoraria; Bayer: Research Funding; Amgen BioPharma: Research Funding; Pfizer: Research Funding. Nagahama: Solasia Pharma: Current Employment, Current equity holder in publicly-traded company. Sonehara: Solasia Pharma: Current Employment, Current equity holder in publicly-traded company. Nagai: Ono Pharmaceutical: Honoraria; Sanofi: Honoraria; Sumitomo Dainippon Pharma: Honoraria; SymBio Pharmaceuticals: Honoraria, Research Funding; Takeda Pharmaceutical: Honoraria, Research Funding; Zenyaku Kogyo: Research Funding; Novartis: Honoraria; Nippon Shinyaku: Research Funding; Mundipharma: Honoraria, Research Funding; Kyowa Kirin: Research Funding; Janssen: Honoraria, Research Funding; Eisai: Honoraria, Research Funding; Chugai Pharmaceutical: Honoraria, Research Funding; Chordia Therapeutics: Honoraria; Celgene: Honoraria, Research Funding; Bristol-Myers Squibb: Honoraria, Research Funding; Bayer: Research Funding; AstraZeneca: Honoraria, Research Funding; AbbVie: Research Funding. Tien: Novartis: Honoraria; Celgene: Honoraria, Research Funding; AbbVie: Honoraria. Tobinai: Ono Pharmaceutical: Consultancy, Honoraria; Solasia Pharma: Honoraria; Mundipharma: Consultancy, Honoraria; Kyowa Kirin: Honoraria; HUYA Bioscience International: Consultancy, Honoraria; Daiichi Sankyo: Consultancy, Honoraria; Eisai: Honoraria; Chugai Pharmaceutical: Honoraria; Celgene: Consultancy, Honoraria; Takeda Pharmaceutical: Consultancy, Honoraria; Zenyaku Kogyo: Consultancy, Honoraria; Yakult: Honoraria. Darinaparsin is an investigational product that is not approved in any country/region in the world.